Factors that contribute to the customer loyalty of Takaful Ikhlas Sdn Bhd / Noryusniza Che Mat Nasir - Che Mat Nasir, Noryusniza (2011)
In today’s competitive marketplace, one of the biggest concerns of service Takaful operations is to winning customer loyalty. This is because the cost of selling to new customers is much higher than the cost of selling to existing customers. Therefore, it is important for the company to foster customer loyalty. Thus, this research is about a study on relationship between factors contributing customer loyalty on Takaful IKHLAS Sdn Bhd. The factors such as customer satisfaction, customer perceived value and corporate image have been identified in order to investigate the current level of customer loyalty of Takaful IKHLAS Sdn Bhd. The survey is conducted at Head Office of Takaful IKHLAS Sdn Bhd. The sample size for this study is 100 customers who are have experience transaction with Takaful IKHLAS Sdn.Bhd. According to this research, the result indicates that the current level of customer loyalty towards Takaful IKHLAS Sdn. Bhd is high. Besides that, the result also indicates that there are significant relationships between all the factors. The most factors contribute to the customer loyalty is corporate image, followed by customer satisfaction and customer perceived value is the last factors contribute to customer loyalty.